(untitled) (World Bulletin of Public Health, 2024)
Constipation is one of the most common complaints and is observed in approximately 3% of children, and in 90% of cases it is functional in nature. In the pathogenesis of chronic constipation, 3 mechanisms are possible: a decrease in propulsive motility and visceral sensitivity of the rectum, as well as a functional impairment of fecal evacuation. Regardless of the specific cause, chronic constipation tends to progress due to overstretching of the intestine and a decrease in its sensitivity. Treatment of functional constipation begins with correction of diet and drinking regimen, and only if these measures are ineffective, bowel cleansing is carried out and laxatives are prescribed.